Матеріали до вивчення рибальського промислу у Дубні в XVI—XVIIІ ст. - Пшеничний, Ю.Л. (Археологія і давня історія України, 2019)
У статті подано огляд нових археологічних та
зооархеологічних джерел, які висвітлюють рибальський промисел на території Дубна в XVI—XVIII ст. Fishery took important place in economic and social
development of Dubno in XVI—XVIII cc. There were
two large ponds around Dubno in that period. Also
they are well-known from historical sources as Surmycky
pond and Ivansky pond. Fishery tools, which were
found during archeological investigations in Dubno
testify about methods of fishing, which were used by
the population of the town. They are led and clay sinkers
for the nets, iron fishing spears and spud, copper
tackle. The fish remains from Dubno castle and Spaso-
Preobrazhensky monastery belonging to eight fish
species (pike, roach, indeterminate carp fish, sturgeon,
common rudd, common bream, european catfish, european
perch). These two prosperous centers had obviously
the largest sizes of cached fishes.